Analysis of the structure and content of professional training future tourism specialists in the field of sports and health tourism in higher education institutions of Ukraine - A. Petrova (Професійна освіта: методологія, теорія та технології, 2023)
The study is devoted to the state of training specialists in active tourism in the context of tourism specialists’ training. The goals of the article are to analyse the structure of educational programs in the specialty «242 Tourism» regarding the availability of sports and health (active) tourism disciplines; to provide quantitative and qualitative characteristics of the educational components of the studied direction. Methods. The study was carried out at the expense of quantitative and qualitative analysis of educational programs and components; comparison, systematization and generalization of the researched material in the specialty 242 Tourism (in the direction of sports and recreation and active tourism). Results. The author analysed forty-one educational programs in the specialty «242 Tourism (Bachelor)», studied educational programs, curricula, work programs of disciplines and educational and production practices in the direction of active tourism. Moreover, the analysis criteria were presented: the presence in the educational program of the profession of active tourism guide; the presence of specialized educational components that form the necessary competencies. As for the educational components of active tourism offered by the institutions, the results of the analysis can be summarized as follows: sixteen institutions offer mandatory educational components; in the context of subjects of free choice ‒ thirteen higher educational institutions; specialized practice (tourist trip) ‒ only five out of forty-one institutions offer on-site training in the form of a trip. Consequently, twenty-four institutions from the general list offer employment as sports and health tourism instructors. Eighteen of them ensure the acquisition of relevant knowledge, skills and abilities. Conclusions. The number of educational programs where sports and health tourism disciplines are mandatory is gradually decreasing. Such a picture indicates a contradiction between the requirements of the state to support and popularize a healthy lifestyle of the nation and the training of specialists in the tourism industry in this direction. As a result, we see the presence (absence) of practitioners in sports and health tourism at specialized departments; the available (absent) material and technical support of specialized departments regarding the organization of theoretical and practical training of sports and health specialists